Effecttiveness of WhatsApp Group on Breastfeeding Practices - Wahidah Sukriani 1,Greiny Arisani 1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Breastmilk is the ideal food for newborn, but in the first days of birth are vulnerable for babiesto be given prelactal food by mother and families. The Successful of exclusive breastfeeding related tovarious factors including media exposure. Mothers who are exposed to the media have more opportunitiesto give exclusive breastfeeding. WhatsApp in a new trend in communication method for giving informationto the public.Objective: This study aims to determine the Effectiveness of WhatsApp Group Towards Pregnant womanin The Practice of First Week Breastfeeding in PalangkarayaMethods: This study is a quasi-experimental study with posttest only with control group design. Purposivesampling technique was used in this study, consisted 36 respondent who were divided into two groups.Analysis were performed by chi-square test.Result: The results showed the average age of respondents was 26.94 years. Most of the respondents werehousewives or unemployed (63.9%), had high and middle education (88.9%) and had high family income(77.7%). Based on statistical test results, WhatsApp Group is effectively used to improve breastfeedingbehavior of mothers in the first week after birth (p <0.05).Conclusion: Health workers are expected to be able to use WhatsApp Group as a health education media onbreastfeeding to increase the scope of exclusive breast milk.